2019
DOI: 10.35864/evmd.549209
|View full text |Cite
|
Sign up to set email alerts
|

Atık yapan sığırlarda Anti-Neospora caninum antikorlarının yaygınlığının araştırılması

Abstract: Bu araştırma sığırların önemli atık etkenlerinden biri olan Neospora caninum'un atık yapmış sığırlardaki yaygınlığının araştırılması amacıyla yapıldı. Bu amaçla, atık geçmişi ile Veteriner Kontrol Merkez Araştırma Enstitüsü Müdürlüğü'ne 25 ilden gönderilen 986 sığır kan serumu N. caninum antikorları yönünden competitive ELISA (c-E-LISA) ile tarandı ve örneklerde %32,35 (319/986) oranında N. caninum tespit edildi. Sığır çiftliklerinde N. caninum kaynaklı enfeksiyonlarda atıklara ilave olarak süt verimlerinde az… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
3
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 25 publications
0
3
1
Order By: Relevance
“…In the current study, the real-time PCR result for the proportion of aborted bovine fetuses infected with N. caninum (48.9%) was considerably higher than those reported from the vicinity of Elazığ in Turkey (25.49%) with the use of duplex PCR [17] and the 35.07% and 32.35% for N. caninum antibodies in cattle in different parts of Turkey reported by Pişkin and Ütük [18] and Erol et al [19], respectively. Anatolian sheepdogs kept with sheep flocks close to cattle herds might be a potential risk factor for bovine infection in the area where the present study was conducted.…”
Section: Discussioncontrasting
confidence: 70%
See 1 more Smart Citation
“…In the current study, the real-time PCR result for the proportion of aborted bovine fetuses infected with N. caninum (48.9%) was considerably higher than those reported from the vicinity of Elazığ in Turkey (25.49%) with the use of duplex PCR [17] and the 35.07% and 32.35% for N. caninum antibodies in cattle in different parts of Turkey reported by Pişkin and Ütük [18] and Erol et al [19], respectively. Anatolian sheepdogs kept with sheep flocks close to cattle herds might be a potential risk factor for bovine infection in the area where the present study was conducted.…”
Section: Discussioncontrasting
confidence: 70%
“…There have been a few molecular studies on bovine neosporosis in parts of Turkey [11,16,17]. In Turkey, seropositivity for N. caninum in cattle in Kars was 8.2% with the use of ELISA [8], 7.01% with cELISA in the Eastern Anatolian region [9], 37.7% with ELISA in some parts of Turkey [11], 35.07% with IFAT in different parts of Turkey [18], 32.35% with cELISA in different parts of Turkey [19], and 7.2% with cELISA in Kars [20].…”
Section: Introductionmentioning
confidence: 99%
“…In this study, it was concluded that the high seropositive rate was due to the detection of the agent on the blood serums brought with the complaint of abortion. Since other reported studies are in the form of field scanning, it is seen that the seropositivity does not exceed 30% (Celik et al, 2013;Erol et al, 2019). As a result, the presence of N. caninum in dairy cows was detected in Aksaray province.…”
Section: Discussionmentioning
confidence: 89%
“…Seropositivity in dairy cows has been reported as 7-33% as a result of studies conducted in different regions in Turkey, which acts as a bridge between Europe and Asia (Kul et al, 2009;Dubey and Schares, 2011;Yıldız. and Gökpınar, 2017;Erol et al, 2019). This suggests that the causative agent may cause diseases that cause significant economic losses in dairy cows.…”
Section: Introductionmentioning
confidence: 99%